Structural characterization of a new high molecular weight polysaccharide from jujube fruit - Ji, Xiaolong; Wang, Zhiwen; Hao, Xiyu; Zhu, Yingying; Lin, Yan; Li, Guoli; Guo, Xudan (Frontiers in Nutrition, 2022)
Ziziphus Jujuba cv. Muzao fruit purified a new high-molecular-weight polysaccharide (PZMP3-1). Constructional characterization showed that PZMP3-1 had a standard molecular weight of 241 kDa, it was composed of 2.56 rhamnose, 7.70 arabinose, 3.73 galactose and 6.73 galactose, respectively. The majorly backbone of PZMP3-1 was consisted of 1,2,4-linked GalpA, 1,4-linked GalpA, 1,4-linked Galp, 1,3-linked Araf, 1,5-linked Araf, and 1-linked Rhap based on methylation and NMR analysis. Structural aspects of PZMP3-1 were examined via FT-IR, XRD, SEM, AFM, and indicated tangled and branched arrangement. Overall, these structural results suggested that PZMP3-1 might imply distinct bioactivities and have considerable utilization in dietary supplements.